Insulin pump therapy is associated with higher rates of mild diabetic ketoacidosis compared to injection therapy: A 2‐year Swedish national survey of children and adolescents with type 1 diabetes. Issue 7 (17th June 2022) - Wersäll, Johan H.; Adolfsson, Peter; Forsander, Gun; Hanas, Ragnar
Abstract: Objectives: Diabetic ketoacidosis (DKA) in type 1 diabetes (T1D) can occur during both insulin pump therapy (continuous subcutaneous insulin infusion, CSII) and insulin injection therapy (multiple daily injections, MDI). The primary aim of this study was to compare CSII and MDI regarding DKA frequency. A secondary aim was to compare metabolic derangement between CSII and MDI at hospital admission for DKA. Research Design and methods: Children 0–17.99 years with established T1D admitted for DKA in Sweden from February 1, 2015 to January 31, 2017 were invited to participate. Data regarding demographics, laboratory data, CSII or MDI, and access to ketone meters and CGM were provided through questionnaires and medical records. The Swedish National Diabetes Registry (SWEDIABKIDS) was used to compare the distribution of CSII and MDI in the national population with the population admitted for DKA, using the chi‐square goodness‐of‐fit test. Distribution of CSII and MDI was then categorized in clinical severity grades for mild (pH 7.20–7.29), moderate (pH 7.10–7.29) and severe DKA (pH <7.10). Results: The distribution of CSII at DKA admission was significantly larger than in the national pediatric population with T1D (74.7% vs. 59.7%, p  = 0.002). CSII was overrepresented in mild DKA (85.2% vs. with CSII, p  < 0.001), but not in moderate/severe DKA (57.9% with CSII, p  = 0.82). Mean HbA1c at hospital admission was 73.9 mmol/mol with CSII and 102.7 mmol/mol with MDI. Conclusions: CSII was associated with higher risk of mild DKA than MDI. MDI was associated with markedly higher HbA1c levels than CSII at hospital admission for DKA.